Cyclic process approach for disposing Islamic literature material in Malaysia: a study - Zainan Nazri, Nurul Jannah; Fatah Yasin, Raudlotul Firdaus; Samsudin, Sofiah; Ghazali, Natirah Azira (Future Academy, 2018)
Despite the vast production of Islamic literature printings every year, little is known about the reality of its disposal process. Is it properly managed? Would it harm the environment? And is there any method other than the burning process?According to the latest statement of Jabatan Kemajuan Islam Malaysia (JAKIM), Jabatan Agama Islam (JAIS) and Jabatan Agama Wilayah Persekutuan (JAWI), they are not able to accept any unused, published Islamic literature materials for disposal for the time being due to the large volume at the collection center. This study involves a serious look at the root causes of the problem and we perceived that the present fatwa and guidelines in Malaysia restricting the disposal method to only burning and disseminating the ashes into the sea as the main reason behind the insufficient space issue at the collection center. Moreover, the protection of environment is a serious concern in Islam. Preservation of environment is not merely an empty word or spoken issue among people. It has to be followed through with actions. This study is an attempt to review the present fatwa and guidelines throughout Malaysia related to the disposing of Islamic literature materials. Concurrently, this study also aims to identify other sustainable means of disposing Islamic literature materials instead of restricting to burning and throwing them into the sea. Last but not least, it aims to propose a new comprehensive guideline for disposing Islamic literature materials.